Effect of Academic, Social, and Personal-emotional Adjustment on Understanding Accounting Courses through Grade Point Average as an Intervening Variable in Development Economics Students at Universitas Negeri Malang - Sahatta, Mahendra Dwianggana; Nasikh, Nasikh; Haryono, Agung (Journal of Education Method and Learning Strategy, 2023)
The transition of students from high school to college experiences several differences including learning methods, learning materials, and new environments. Adaptation or self-adjustment is needed in new students, from existing adaptations, it is developed to understand accounting courses because accounting is important for the world of work for both educators and non-educators. Initial observations made by students have good GPA scores, have good relationships with each other, but are still not maximized in the value of accounting course assignments, and still experience psychological problems when doing assignments. This study uses a quantitative approach with an explanatory type of research. The population used in this study is 2nd-semester students majoring in development economics who have taken introductory accounting and financial accounting courses. The sampling technique used a random sampling system of 92 students. Data collection using questionnaires and test tests. The data analysis used is descriptive statistics, inner model, outer model, path analysis, and Structural Equation Modeling (SEM) analysis with Smart-PLS 4. The results showed that the direct effect, namely: variable X1 has no effect on Y, variable X2 has an effect on Y, variable X3 has an effect on Y, variable X1 has no effect on Z, variable X2 has an effect on Z, variable X3 has an effect on Z and variable Y has an effect on Z while in indirect effects, namely: variable X1 has no effect on Y through Z, variable X2 affects Y through Z and variable X3 affects Y through Z